The Effect of Methanolic Extract and Ethyl Acetate Fraction of Kepel Fruit (Stelechocarpus burahol) to α-Glutathione S-Transferase Enzyme Concentration of Rat Liver and Blood Induced by CCl4 - Yusuf Rabbani; Claude Mona Airin; Sugeng Riyanto (Institute for Halal Industry and System (IHIS) Universitas Gadjah Mada, 2020)
Degenerative diseases are mostly caused by high free radical concentrations in the body. Kepel fruit(Stelechocarpus burahol) is known to contain flavonoid compounds, a class of compounds that has free radicalscavenging activity in the body and could affect the activity of antioxidant enzymes. There have been reportsthat methanolic extract and ethyl acetate fractions of Kepel fruit have the lowest IC50 values, compared toextracts or fractions which are made using other organic solvents, on in vitro assays so that flavonoids aresuspected as responsible compounds to the free radical scavenging activity. This study aimed to identify thepresence of flavonoid content in methanolic extract and the fraction of ethyl acetate of Kepel fruit and also itseffect on rat alpha Glutathione S-Transferase (α-GST) enzyme concentration for the function to prevent hepaticcell damage due to carbon tetrachloride exposure. The identification of flavonoids content used a series ofcolor chemical reaction tests and thin layer chromatography that used silica gel 60F254 as the solid phase andmixture of ethyl acetate, formic acid, glacial acetic acid, and water (100: 11 : 11: 20 v/v) as the mobile phase.This study used 30 Sprague-Dawley female rats (age 2-3 months) that were grouped into 5 groups as solventcontrol (CMC-Na) group, negative control (CCl4) group, positive control (vitamin C) group, methanolic extractgroup, and ethyl acetate fraction group. All groups were induced with carbon tetrachloride (CCl4) compoundsexcept for the CMC-Na solvent control group. Blood sampling at 0 h, 24 h, and 72 h, while liver sampling at 24h and 72 h, with 3 samples each group. The analysis of rat α-GST enzyme concentrations used theEnzyme-linked Immunosorbent Assay (ELISA) method. Based on the phytochemical test, the methanolicextract and the ethyl acetate fraction of Kepel fruit have been identified contains flavonoids compound. Basedon the in vivo study, the positive control group's α-GST enzyme concentration was decreased, while thenegative control group's α-GST enzyme concentration was increased. Administration of methanolic extractand ethyl acetate fraction also decreased both liver and blood rat α-GST enzyme concentrations, althoughwithout significant correlation, and still could prevent the hepatic cell damage due to carbon tetrachlorideexposure.